METHODS OF TEACHING THE NATIVE LANGUAGE (World Bulletin of Social Sciences, 2023)
The principles of the methodology of teaching the native language based on the task of teaching students the native language, their upbringing and comprehensive development, based on the theory of cognition, based on the recommendations of all close, interconnected disciplines, the methodology of teaching the native language develops its principles. These principles are different from universal principles and determine the directions of Educational Labor between the teacher and the student. In this article, feedback and feedback on the teaching of the subject of the native language will be made. comprehension processes of the native language and reading literacy textbooks in increasing reading literacy of Primary School students